“Has this been tested? Who has it helped? Who has it hurt?”: Public perceptions about California’s extreme risk protection order law - Nicole Kravitz-Wirtz; Alexandra Dent; Shani Buggs; Amanda J. Aubel; Julia Lund; Garen Wintemute; Veronica A. Pear (PLoS ONE, 2025)
Extreme risk protection order (ERPO) laws in the United States temporarily suspend access to firearms by individuals judged to be at significant risk of harm to self or others. Evidence points toward preventive effects, but uptake of these laws remains lower than that which is likely needed to optimize their intended benefits on rates of firearm-related injury. To inform implementation efforts and policy refinements, we examined public awareness of and support for California’s ERPO law, barriers to its use, and possible alternative approaches. Using a general population sample of adults from the California Safety and Wellbeing Survey ( N = 3531), with both closed-ended and open-ended questions, we provide updated prevalence estimates and narrative insights about the policy, with subgroup analyses by firearm ownership status and categories of race and ethnicity. Most respondents remained unaware of the law; however, after reading a brief policy description, majorities of the population, including firearm owners and respondents across all racial-ethnic subgroups, endorsed ERPOs as appropriate and said they would be willing to serve as petitioners for family members of concern. Barriers to use included knowledge gaps, particularly among non-firearm owners and Black, Latine, and Asian respondents; not trusting the system to be fair; and the perception that the scenarios of concern involved personal or family matters. More than one-third of respondents said the police were not a preferred means through which to initiate an order and a similar proportion favored holding onto a family member’s guns themselves instead of using an ERPO. Optimizing the lifesaving impacts of ERPOs will require addressing these layered concerns through coordinated and sustained investments in broader ecosystems of community safety while still facilitating firearm recovery where appropriate.